An ethical issue in anti-commons management. Aquaculture case in Portugal - Filipe, J. (2017)
Ethical problems are a very relevant issue present in many aspects of real life. These situations can be examined through several branches and under several ways or grids of analysis, modern or classic. The relationship among people, either in business or current life management, involves problematic aspects in real life situations, which have often ethical consequences. Anti-Commons Theory is a very recent development in the area of property rights. It intends to explain why an “anti-commons” emerges and why resources may be prone to under-use. In an anti-commons situation there are too many exclusion rights that lead to the under-use of resources. In Portugal, too many people (and institutions) are involved in the approval processes of aquaculture projects. They may be involved in reaching a decision about the approval of a project which gives rise to the underutilization of the resources that promoters aimed to exploit. In fact, it takes so long to approve a project that the time required for its implementation is excessively delayed. An ethical problem rises with this phenomenon. In these cases, projects may not go forward and all the amounts spent in the project will be lost. Often, a viable project simply is gone, with the inherent losses of value.